ANALISIS KEPUASAN JAMINAN KESEHATAN NASIONAL PADA PENGGUNA BPJS KESEHATAN DI KOTA SEMARANG (Unnes Journal of Public Health, 2017)
National health insurance (NHI) as a part of national social security system (NSIS) is a form of government commitment to the implementation of health insurance among people in Indonesia entirely. State-owned enterprises (SOEs) assigned specifically by the government to provide health care insurance was the BPJS for Health (social security provider for health). The aim of this study was to analyze the satisfaction of national health insurance among BPJS for Health participants in Semarang City based on education, tuition classes, and place of service. This study was analytical survey with cross sectional approach. Sample of Non PBI (Contribution Assistance Recipients) BPJS for Health were 269 respondents, with purposive proportional sampling technique. There was a significant difference regarding the satisfaction of health insurance based on education level (basic, secondary, and high) and place of service (public hospital and private hospital). There was no significant difference on satisfaction of health insurance based on tuition classes (class I, II, and III). BPJS for Health participants who did not satisfied with the national health insurance were 64.7%. The most important complaint was the process of obtaining an inpatient room.